Hubungan Gaya Kepemimpinan Kepala Sekolah Dengan Efektivitas Sekolah Menengah Atas Negeri Se–Kota Palangka Raya - Suniati Suniati (Anterior Jurnal, 2014)
This research was conducted at State Senior High Schools in Palangka Raya, Central Kalimantan, the purpose of this research is to know whether there is any significant relationship between Headmasters’ Leadership Style toward the school effectiveness at State Senior high Schools in Palangka Raya simultaneously. This research was designed by using the correlation quantitative approach through survey method. The target population is all teachers at State Senior High Schools in Palangka Raya, which amount to 163 teachers. The total number of research sample was 115 teachers. The sample was taken by using randomized proportional sampling technique. The result of this research conclude that there was a significant relationship between Headmasters’ Leadership Style with the School Effectiveness, represented by the linear regression Ŷ= a + bX = 23,21 + 0,77X and correlation coefficient ry = 0.963 which is significant at α = 0,05. This result of this study is expected to be useful for improving the school effectiveness in achieving its vision and mission of the objective of an effective and efficient school. The director behavior leadership of school can empower the teachers to implement the process of learning a good, soft, and production, and management to implement the appropriate principles of leadership with the level of maturity of teachers and others school employees.